CYTOKINEMIA IN ADHESIONS OF THE ABDOMINAL CAVITY AND ITS COMPLICATIONS IN ELDERLY AND SENILE PATIENTS - Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2026)
The high incidence of acute commissural small bowel obstruction and its complications in elderly patients is accompanied by an increase in postoperative mortality, which is based on immune system disorders. We set ourselves the goal of determining the degree of cytokinemia development in patients with various forms of abdominal adhesions. At the same time, among the analyzed cohorts of patients, we also identified patients with acute adhesions, small intestinal obstruction and a form complicated by peritonitis. In the blood of patients, we study the concentration of interleukins, which belong to the group of pro-inflammatory. We found that changes in the concentration of interleukins in the blood depend on the pathology being analyzed, related to intestinal obstruction or the development of peritonitis.